CoSnO3/C nanocubes with oxygen vacancy as high-capacity cathode materials for rechargeable aluminum batteries - Shuainan Guo; Mingquan Liu; Haoyi Yang; Xin Feng; Ying Bai; Chuan Wu (Green Energy & Environment, 2023)
Rechargeable aluminum batteries (RABs) are attractive cadidates for next-generation energy storage and conversion, due to the low cost and high safety of Al resources, and high capacity of metal Al based on the three-electrons reaction mechanism. However, the development of RABs is greatly limited, because of the lack of advanced cathode materials, and their complicated and unclear reaction mechanisms. Exploring the novel nanostructured transition metal and carbon composites is an effective route for obtaining ideal cathode materials. In this work, we synthesize porous CoSnO3/C nanocubes with oxygen vacancies for utilizing as cathodes in RABs for the first time. The intrinsic structure stability of the mixed metal cations and carbon coating can improve the cycling performance of cathodes by regulating the internal strains of the electrodes during volume expansion. The nanocubes with porous structures contribute to fast mass transportation which improves the rate capability. In addition to this, abundant oxygen vacancies promote the adsorption affinity of cathodes, which improves storage capacity. As a result, the CoSnO3/C cathodes display an excellent reversible capacity of 292.1 mAh g−1 at 0.1 A g−1, a good rate performance with 109 mAh g−1 that is maintained even at 1 A g−1 and the provided stable cycling behavior for 500 cycles. Besides, a mechanism of intercalation of Al3+ within CoSnO3/C cathode is proposed for the electrochemical process. Overall, this work provides a step toward the development of advanced cathode materials for RABs by engineering novel nanostructured mixed transition-metal oxides with carbon composite and proposes novel insights into chemistry for RABs.